Four hurdles for conservation on private land: the case of the golden lion tamarin in Brazil's Atlantic Forest - Buckley, Ralf C.; de Vasconcellos Pegas, Fernanda (Frontiers in Ecology and Evolution, 2015)
Many threatened species worldwide rely on patches of remnant vegetation in private landholdings. To establish private reserves that contribute effectively to conservation involves a wide range of complex and interacting ecological, legal, social, and financial factors. These can be seen as a series of successive hurdles, each with multiple bars, which must all be surmounted. The golden lion tamarin, Leontopithecus rosalia, is restricted to the Atlantic Forest biome in the state of Rio de Janeiro, Brazil. This forest is largely cleared. There are many small remnant patches on private lands, able to support tamarins. Local NGO's have successfully used limited funds to contribute to tamarin conservation in a highly cost effective way. We examined the mechanisms by analysing documents and interviewing landholders and other stakeholders. We found that the local NGOs successfully identified landholdings where ecological, legal, social, and some financial hurdles had already been crossed, and helped landholders over the final financial hurdle by funding critical cost components. This cost < 5% of the price of outright land purchase. This approach is scalable for golden lion tamarin elsewhere within the Atlantic Forest biome, and applicable for other species and ecosystems worldwide.